2013
DOI: 10.1080/09593330.2012.696717
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide and methane emissions from different treatment processes in full-scale municipal wastewater treatment plants

Abstract: Nitrous oxide (N2O) and methane (CH4) are two important greenhouse gases (GHG) emitted from biological nutrient removal (BNR) processes in municipal wastewater treatment plants (WWTP). In this study, three typical biological wastewater treatment processes were studied in WWTP of Northern China: pre-anaerobic carrousel oxidation ditch (A+OD) process, pre-anoxic anaerobic-anoxic-oxic (A-A/ A/O) process and reverse anaerobic-anoxic-oxic (r-A/ A/O) process. The N2O and CH4 emissions from these three different proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 35 publications
(42 reference statements)
1
28
0
Order By: Relevance
“…These authors also suggested that the methanogens found in the aerated WWT plants investigated in their study may simply survive under oxygen exposure and be restricted in their activity to the anoxic areas of the plants, or just play structural roles in cell-aggregate development as they are proposed to do in GS. Archaea have also been detected in other aerated WWT systems [7276]. …”
Section: Archaeal Communities In Anaerobic Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also suggested that the methanogens found in the aerated WWT plants investigated in their study may simply survive under oxygen exposure and be restricted in their activity to the anoxic areas of the plants, or just play structural roles in cell-aggregate development as they are proposed to do in GS. Archaea have also been detected in other aerated WWT systems [7276]. …”
Section: Archaeal Communities In Anaerobic Bioreactorsmentioning
confidence: 99%
“…Despite their strictly anaerobic metabolism, it has been found that methanogenic Archaea are often part of the microbiota of aerated WWT systems [7276], and a few studies have also reported their presence in aerated MBR [16,102]. The presence of anaerobic Archaea under aerated conditions is explained by the anoxic microenvironments created by the flocs’ stratification, located in the core of the aggregates.…”
Section: Archaea In Biofilms Formed In Membrane Bioreactors (Mbr) mentioning
confidence: 99%
“…Direct GHG emissions from OD processes have not been measured in this study but nitrous oxide and methane emissions are of relevance and should be accounted for. [21] Ferric chloride was dosed at Site 2 and it was assumed it would still be dosed, however, it is also expected that this would now be prior to the use of the PSTs instead of prior to the OD, and therefore this value was not affected. The size, number and capital cost of the PSTs required to treat the influent in Site 2 was completed using Southern Water design and cost models.…”
Section: Recommendations For Site 2 Optimizationmentioning
confidence: 99%
“…The IPCC Guidelines take a first principles approach to estimating wastewater CH 4 emissions based on the maximum CH 4 yield from a given quantity of organics and a correction factor to account for the likely realization of this maximum CH 4 production along a given treatment and discharge pathway (Doorn et al, 2006). Compared to N 2 O, CH 4 emissions from wastewater systems have been much less well researched and there are relatively few published studies (Wang et al, 2011a;Ren et al, 2013;Willis et al, 2012;Daelman et al, 2013). Compared to N 2 O, CH 4 emissions from wastewater systems have been much less well researched and there are relatively few published studies (Wang et al, 2011a;Ren et al, 2013;Willis et al, 2012;Daelman et al, 2013).…”
Section: Chmentioning
confidence: 99%